Mechanical and Thermophysical Properties of Neptunium Monopnictides - Singh, Devraj; Kaushik, Shivani; Pandey, Sunil Kumar; Mishra, Giridhar; Bhalla, Vyoma (VNU Journal of Science: Mathematics - Physics, 2016)
Abstract: The temperature dependent ultrasonic parameters like ultrasonic attenuation, acoustic coupling constant, ultrasonic Grüneisen parameter and ultrasonic velocity at room temperature have been computed for neptunium monopnictides (NpX, where X=N, P, As, Sb). For the evaluation of ultrasonic parameters, the higher order elastic constants have been found out using Coulomb and Born-Mayer potential up to second nearest neighbour in the temperature range 0-300K. In addition to this, some mechanical constants like bulk modulus, Young’s modulus and Poisson’s ratio are also evaluated at room temperature to find their mechanical stability. The toughness to fracture ratio is found to be 0.571 which clearly shows brittle nature of NpX. Born criterion of mechanical stability is also followed by these materials. Neptunium nitride is most stable and durable material due to its high valued elastic constants. In present investigation, the thermal conductivity of these materials is also evaluated using Slack’s approach.  The ultrasonic attenuation due to thermoelastic relaxation mechanism is negligible in comparison to phonon-phonon interaction mechanism. The achieved investigation results on NpX materials are discussed and compared with other similar type of materials. Keywords: Monopnictides, Elastic properties, Ultrasonic properties, Thermal conductivity.